PEMIKIRAN METODOLOGIS MAZHAB FIKIH DAN PENGARUHNYA TERHADAP PEMBENTUKAN HUKUM ISLAM DI INDONESIA - Ahmad Supiannor; Anwar Hafidzi (Al Arsy: Journal of Education, Management and Islamic Thought, 2025)
This research examines the scope of the methodological thought of various fiqh schools and their influence on the formation of Islamic law in Indonesia. The objective is to analyze the epistemological characteristics of each school and their practical relevance to the development of national law. This study employs a normative (doctrinal) research method with conceptual and statutory approaches, utilizing qualitative analysis of primary and secondary data. The results reveal that each school has distinct istinbath mechanisms, such as istihsan in Hanafi, maslahah mursalah in Maliki, istidlal in Shafi’i, and strict textual commitment in Hanbali and Zhahiri. These methodologies significantly shaped the Compilation of Islamic Law (KHI), which functions as a cross-school synthesis (manhaj muqaran) through takhayyur and talfiq. While the Shafi’i school remains dominant due to historical factors, the KHI integrates diverse views to address modern social needs. In conclusion, the methodological diversity of fiqh schools provides an authoritative yet flexible foundation, allowing Islamic law in Indonesia to operate as a responsive "living law" while remaining rooted in Sharia principles